Association of Soluble Suppression of Tumorigenesis 2 (sST2) With Platelet Activation, Monocyte Tissue Factor and Ischemic Outcomes Following Angioplasty and Stenting - Stojkovic, Stefan; Demyanets, Svitlana; Kopp, Christoph W.; Hengstenberg, Christian; Wojta, Johann; Eichelberger, Beate; Panzer, Simon; Gremmel, Thomas (Frontiers in Cardiovascular Medicine, 2020)
Background: Peripheral artery disease (PAD) patients undergoing infrainguinal angioplasty with stenting suffer high rates of target lesion restenosis and ischemic events. Blood-based prognostic markers in these patients are currently limited. The IL-33/ST2-system is involved in atherothrombosis. Soluble ST2 has been proposed as a biomarker in patients with cardiovascular disease. Aim: To investigate the association of sST2 with platelet activation and monocyte tissue factor (TF) in 316 patients undergoing elective angioplasty and stenting for cardiovascular disease, and its predictive value for ischemic outcomes following infrainguinal angioplasty with stent implantation in 104 PAD patients within this cohort. Methods and results. Circulating levels of sST2, platelet surface P-selectin, monocyte TF expression as well as soluble P-selectin were determined in 316 consecutive patients on dual antiplatelet therapy following angioplasty and stenting. sST2 was independently associated with soluble P-selectin (B=6.4, 95% CI 2.0 – 10.7, p=0.004) and TF expression (B=0.56, 95% CI 0.02 – 1.1, p=0.041) but not with platelet surface P-selectin (B=0.1, 95% CI -0.1 – 0.3, p=0.307) after adjustment for age, sex, clinical risk factors and inflammatory parameters. During the follow-up of 24 months, the primary endpoint occurred in 41 of 104 PAD patients (39.4%). However, circulating levels of sST2 did not predict the primary endpoint in PAD patients (HR 1.1, 95% CI 0.76 – 1.71, p=0.527). Conclusion. sST2 is associated with soluble P-selectin and monocyte TF expression in atherosclerosis but not with ischemic outcomes following infrainguinal angioplasty with stent implantation for PAD.